Discovery of immunoglobulin T in Nile tilapia (Oreochromis niloticus): A potential molecular marker to understand mucosal immunity in this species. (November 2018) - Velázquez, Janet; Acosta, Jannel; Lugo, Juana María; Reyes, Eduardo; Herrera, Fidel; González, Osmany; Morales, Antonio; Carpio, Yamila; Estrada, Mario Pablo
Abstract: Immunoglobulin molecules play an important role in the immune defense system in all jawed vertebrates, by protecting the organism from a wide variety of pathogens. Nile tilapia ( Oreochromis niloticus ) is extensively cultivated worldwide, with a strong established market demand. It constitutes one of the model species for the study of fish immunology and its genome is currently fully sequenced. The presence of the immunoglobulin M gene in this species is well documented, as well as its major role in systemic immunity. To date, the IgT gene from O. niloticus has not been identified and, therefore, no information is available on the role of this immunoglobulin isotype in the immune response in tilapia. In the present work, novel secreted and membrane immunoglobulin T isotypes and a fragment of IgM were isolated from tilapia head kidney lymphocytes. Their transcriptional profiles were analyzed by quantitative PCR in larval development and in different tissues of healthy or lipopolysaccharide/ Edwardsiella tarda -challenged tilapia adults. The presence of IgT and IgM were detected in early stages of larval development. Additionally, these genes exhibited differential expression profiles in basal conditions and after E. tarda infection in adult tilapia, in accord with the proposed effector functions of these immunoglobulins in the systemic and mucosal compartments. Our results suggest the potential involvement of this new Ig in mucosal immunity in tilapia. Highlights: Two novel isoforms of IgT were cloned from Nile tilapia head kidney lymphocytes. The isolated cDNA sequence has the typical features of IgT. Early expression of IgT and IgM was detected in tilapia larvae. IgT and IgM are differentially expressed in basal conditions and after E. tarda infection. Infection by immersion suggested IgT specialization in mucosal compartments.